2002
DOI: 10.2105/ajph.92.9.1462
|View full text |Cite
|
Sign up to set email alerts
|

Welfare to Work? Impact of Maternal Health on Employment

Abstract: Poor maternal health is associated with need for cash assistance and health insurance. Policymakers must recognize that social policies promoting employment will fail if they do not address the health needs of poor women and children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 12 publications
(7 reference statements)
1
36
0
Order By: Relevance
“…NIH-PA Author Manuscript NIH-PA Author Manuscript lower rates of current employment, but no significant differences in their employment patterns over the past 3 years (Romero, Chavkin, Wise, Smith, & Wood, 2002).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 98%
“…NIH-PA Author Manuscript NIH-PA Author Manuscript lower rates of current employment, but no significant differences in their employment patterns over the past 3 years (Romero, Chavkin, Wise, Smith, & Wood, 2002).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 98%
“…6 Americans, particularly those in low-income racial/ethnic minority groups, have higher death rates from coronary heart disease, cancer, diabetes, and injury, and these rates have been linked to gender, access to care, and health insurance coverage. 20,59,93,95-98 TANF has not had a notable impact on reducing this disparity, and it continues to be a public health issue.…”
Section: Effects Of Termination On Other Benefitsmentioning
confidence: 99%
“…Results of study after study suggest that the low-income population served by TANF is less educated and poorer than the low-income population not enrolled in TANF and has a high prevalence of mental and physical health problems that persist over time and limit the ability to work. 4,11,58,59,63,78,96,[99][100][101][102][103][104][105][106] found that 35% of Women's Employment Study respondents met the criteria for at least 1 of the 5 diagnoses. These reports drew on data from the earlier years of the TANF program.…”
Section: Effects Of Termination On Other Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women on welfare represent one of the most disadvantaged segments of our society; 39% of are single African American women with children (Parvez, 2002). The prevalence of mental and physical health problems, depression, and obesity, is higher among welfare recipients than other populations (Romero, Chavkin, Wise, Smith, & Wood, 2002). Moreover, African American women reportedly have more mental and physical health problems than women of other races (Corcoran, Danziger, & Tolman, 2003).…”
Section: Overviewmentioning
confidence: 96%